Documentation and exhibition of landscape heritage: learnings from analogue to digital techniques - Zakariya, Khalilah; Nizarudin, Norhanis Diyana; Md Jani, Haza Hanurhaza; Ibrahim, Putri Haryati; Harun, Nor Zalina (Prince of Songkla University, Pattani Campus, 2023)
Documentation is a vital process of learning about heritage. The tangible and intangible legacies of a society and a place can be recorded through texts, drawings, maps, photographs, videos, audio, products, artefacts and other means to create narratives that could be shared to foster intergenerational knowledge transfer on heritage. As the use of technology becomes more common, the techniques of documentation and exhibition for heritage have also evolved. This study aims to examine how the techniques of documentation and exhibition have shifted from analogue to digital integration. This study draws upon seven projects on landscape heritage conducted in Malaysia and Indonesia as part of the landscape architecture undergraduate programme. The documentation and exhibition techniques employed in each project are categorised based on their instruments, processes, and output. The forms of documentation are then analysed based on their potentials and constraints in recording and exhibiting the projects’ findings effectively and efficiently. The study found that the combination of analogue and digital techniques has more advantages for heritage documentation. The learnings gained from conducting these projects using the various techniques have underscored the importance of reflection, evaluation, exploration, adaptation, and refinement in the process of heritage documentation.